Izgovor črke kot jezikoslovno vprašanje do konca 19. stoletja - Horjak, Luka (Jezik in slovstvo, 2021)
After the Protestant era, discrepancies arose between the written and spoken form of the Slovenian language. The most significant discrepancy concerned the pronunciation of the letter , because the phoneme /ł/ became bilabial u. Every grammarian has pointed out the discrepancies between the written and spoken form in their own way with lists of rules or exceptions. In the written form, they retain the traditional Protestant orthography. The nineteenth century saw the appearance of the first guidance for foreigners regarding the pronunciation of the letter , which recommended always pronouncing the it as l. The most common argument mentioned was the proximity with other Slavic languages. From the end of the nineteenth century, "reading by the letter" was prescribed for schools and was viewed as a status symbol of the bourgeoisie. This phenomenon is known as "elkanje". However, Stanislav Škrabec opposed this prescription. His aspirations for the so-called natural pronunciation were first realised with the first Slovenian orthography Slovenski pravopis by Fran Levec in 1899. In the twenty-first century, the concept of "speech by the letter" is again gaining supporters.
Keywords: 19. stoletje; 19th century; elkanje; reading by the letter; Slovenian; slovenščina; Škrabec, Stanislav